Pengaruh Model Problem Based Learning dan Problem Solving terhadap Kemampuan Pemecahan Masalah Mupel IPA Kelas IV Sekolah Dasar Gugus Sembodro - Pramesti Wardani; Wasitohadi - (Peneliti.net, 2020)
The purpose of this study was to determine the effect of problem based learning and problem solving models on the problem solving abilities of class IV elementary school students. This research method uses quasi-experimental (Quasi-Experimental Design) with Pre-test Post-test using the Non-equivalent Control Group Design and using cluster sampling techniques. The subjects of the study were the fourth grade students of SDN Mukiran 03 as the experimental class who were treated using the problem based learning model and the fourth-grade students of SDN Mukiran 04 as the control class who were treated using the problem solving model. The data analysis technique used is descriptive and inferential statistics with the help of SPSS 24. The average difference test results indicate there are significant differences in influence between students who are treated with problem based learning models and students who use problem solving models. Significant differences in the two models can be seen from the average pre-test and post-test problem-solving abilities of the two classes. The result is obtained by a pre-test average difference test with a significance of 0.463> 0.05, which means there is no difference in the learning outcomes of the experimental class and the control class and the results of the post-test mean a difference in the significant value of 0.011 <0.05 which it means that there are differences in learning outcomes in the experimental class and the control class. The problem-solving ability of the experimental class students is higher than the control class. So it can be concluded that the model of problem-based learning affects the ability of problem-solving of fourth-grade students of elementary schools.